If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12x+x=(4x+8)(3x-3)
We move all terms to the left:
12x+x-((4x+8)(3x-3))=0
We add all the numbers together, and all the variables
13x-((4x+8)(3x-3))=0
We multiply parentheses ..
-((+12x^2-12x+24x-24))+13x=0
We calculate terms in parentheses: -((+12x^2-12x+24x-24)), so:We add all the numbers together, and all the variables
(+12x^2-12x+24x-24)
We get rid of parentheses
12x^2-12x+24x-24
We add all the numbers together, and all the variables
12x^2+12x-24
Back to the equation:
-(12x^2+12x-24)
13x-(12x^2+12x-24)=0
We get rid of parentheses
-12x^2+13x-12x+24=0
We add all the numbers together, and all the variables
-12x^2+x+24=0
a = -12; b = 1; c = +24;
Δ = b2-4ac
Δ = 12-4·(-12)·24
Δ = 1153
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(1)-\sqrt{1153}}{2*-12}=\frac{-1-\sqrt{1153}}{-24} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(1)+\sqrt{1153}}{2*-12}=\frac{-1+\sqrt{1153}}{-24} $
| 105-(3p-18)=90 | | 9x^2-6=94 | | Y=9/4x+11/9 | | 8(-5t-6)+2t=8(-3t+1) | | 1.8(x+2)=2x+16 | | Y=-4/9x+11/9 | | 2(z+1)=-4(z-4) | | -4-8r=-7r+1 | | 7m^2=196 | | 3/4+c=1/4 | | 36/x=28/(16-x) | | 6n*2-2n-3+5n*2-9n=6 | | Y=-9/4x+11/9 | | -3=-1.5(k+9.2) | | -8(m+1)=40 | | 26+5s=-6(8s-7) | | 2(w+6)+(-6)=-4 | | 12x-5=94 | | 2(w+6)+–6=–4 | | 10x-1+7x+7=125 | | 13x+3+35=180 | | -8(m+11)=40 | | w(2w-8)=90 | | w(2w-8)=9 | | (7x-6)+(6x+15)=180 | | 0=s+7 | | 11x+14=7x+39 | | -4(8+5x)=25 | | 6(x+10)=2(x+30)+4x | | 10(x-8)=5(2x-16) | | 4x-4=10+2x | | 8a+4-3a+6=2a+2a+8+8 |